ORIGINAL PAPER The role of intraoperative transesophageal echocardiography in tricuspid valve annuloplasty – 15 years follow-up (1988-2003) - Kośmider, Anna; Banach, Maciej; Zasłonka, Janusz; Walczak, Andrzej; Zwoliński, Radosław; Kośmider, Maciej (Archives of Medical Science, 2005)
Objectives: Tricuspid valve regurgitation is usually secondary and results from the changes in geometry of tricuspid annulus, dilatation or overload of right atrium and right ventricle. The aim of the study was the assessment of early and long-term results of tricuspid valve annuloplasty performed in the Department of Cardiac Surgery in Lodz, Poland between 1988-2003. Design: The study group consisted of 267 patients with tricuspid valve regurgitation. Tricuspid valve annuloplasty was performed using two methods: De Vega in 70 patients (26.2%) and Revuelta in 197 patients (73.8%). All patients were referred to tricuspid surgery on the ground of classic echocardiography and in 92 cases transoesophageal echocardiography was necessary to verify diagnosis. Intraoperative transoesophageal echocardiography was performed in 162 patients (60,7%). Results: Throughout the long-term follow-up rates of patients with good result of tricuspid annuloplasty were: 86% after 5 years, 45% after 12 years, and 40% after 15 years. Since 1997, due to excellent results, tricuspid annuloplasty has been performed using Revuelta procedure only. Within 6-years follow-up after tricuspid annuloplasty a necessity of reoperation was observed in 19 patients (7.1%) from a subgroup without intraoperative transoesophageal echocardiography and in only 2 (0.75%) from a subgroup with transoesophageal echocardiography monitoring. Conclusion: Intraoperative transoesophageal echocardiography seems to be a method of choice in assessment of tricuspid annuloplasty efficacy which was confirmed by the long-term outcomes. Tricuspid valve annuloplasty using Revuelta procedure, intraoperatively verified by transoesophageal echocardiography, is currently a standard method in our department. Pulmonary hypertension and deteriorated systolic and diastolic right ventricular function yield with worse long-term results.